Desenvolvimento de protótipo de sensor de umidade cerâmico - Ito, Amadeu Rodrigues Pereira (Universidade Federal de São Carlos, 2012)
Humidity sensor is a special type of gas sensor which is sensitive only to H2O molecules. It has a large variety of applications in industrial, household and agricultural equipments. Humidity ceramic sensors have been considered interesting due to their chemical and thermal stability. The lack of a national manufacturer of humidity sensors was the main motivation to accomplish this master thesis, whose objective was to develop a prototype of resistive ceramic humidity sensor. The objective was reached using Mn doped-MgAl2O4 powder, forming thin plates (650 a 750 μm) through tape casting process, appropriate sintering to obtain proper microstructure and the performance characterization of sintered plates as humidity sensor, especially with regard to sensibility and reproducibility. The tape casting process was successful for providing plates with excellent sensibility in the range 20-90% relative humidity and the response time of 120 and 20 seconds in the adsorption and desorption steps respectively. The correlation between the good performance and the porosity was established through the detailed interpretation of impedance spectra measured at several levels of humidity. Simultaneously to the porous plate preparation, it was developed a microcontrolled electronic transducer circuit with firmware written in C, which allows the immediate use of the electric signal produced by the humidity sensitive plate by a variety of equipments already available in the market. At the final step, the humidity sensor prototype was assembled through the insertion of the humidity sensitive plate, appropriately covered with silver electrode, to the electronic system.
Development of ceramic humidity sensor prototype
Keywords: Umidade; Sensor; Cerâmica; Transdutor; Humidity; Ceramics; Transducer; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA